Zimbabwe’s land reform programme, migration and identity in Lawrence Hoba’s The Trek and other stories - Musanga, Terrence (Taylor & Francis (Routledge), 2016)
Zimbabwe’s land reform programme in 2000 has generated a lot of local, regional and global attention complemented by a surge of historical and sociological analysis of the land question in Zimbabwean society. In addition to this coverage and analysis, the land reform programme also polarised people within and outside the country with some viewing it as a revolutionary and progressive move in the decolonisation of the country. Others, conversely, object to this narrative and project it as the suicidal actions of a government disrespectful of property rights and desperate to cling onto power. This perspective perceives the programme as inherently chaotic and a key moment in what has come to be known as the Zimbabwean crisis which imploded post 2000. However, what is often occluded in these studies is the fact that central to the land reform programme is migration and the attendant identity (re)formation. These are the issues underscored in my examination of Lawrence Hoba’s The Trek and Other Stories.